Optical Fiber Communication Conference 2014
DOI: 10.1364/ofc.2014.tu3a.2
|View full text |Cite
|
Sign up to set email alerts
|

Time-Division Hybrid Modulation Formats: Tx Operation Strategies and Countermeasures to Nonlinear Propagation

Abstract: We propose four strategies for TDHMF Tx operation. BER minimization permits PM-QPSK/PM-16QAM performance similar to PM-8QAM's. In TDHMF nonlinear propagation, predistortion and/or polarization interleaving enables the maximum reach predicted by GN-model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Zhuge et al [6][14] [15] successfully demonstrated the TDHM transmission in the environments of both fixed grids and future flex-grids by employing high-speed digital to analogue converters (DACs) at transmitters and low-complexity digital signal processors (DSPs) at receivers. Curri et al [16] investigated the transmitter operation strategies for the TDHM technique and showed pre-distortion and polarization interleaving can help alleviate the penalty induced by nonlinear propagation.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhuge et al [6][14] [15] successfully demonstrated the TDHM transmission in the environments of both fixed grids and future flex-grids by employing high-speed digital to analogue converters (DACs) at transmitters and low-complexity digital signal processors (DSPs) at receivers. Curri et al [16] investigated the transmitter operation strategies for the TDHM technique and showed pre-distortion and polarization interleaving can help alleviate the penalty induced by nonlinear propagation.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Constraint (15) ensures that there is maximally only one working lightpath channel occupying a wavelength in any fiber link. Constraint (16) ensures the condition of spare capacity sharing among protection lightpath channels. Constraint (17) ensures that each wavelength in any fiber link can only be used by either a working lightpath channel or a protection lightpath channel.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular PDM 2 m -ary QAM modulation formats like BPSK, QPSK, 8QAM and 16QAM (with m = 1, 2, 3, 4 bits/symbol, respectively) allow only certain data-rates for a specific FEC code rate. A possible candidate to provide finer granularity in SE is TDHQ [4,[10][11][12][13]. It is based on the assignment of two or more regular 2 m -ary QAMs with different SEs in alternating symbol times.…”
Section: A Time-domain Hybrid Qammentioning
confidence: 99%
“…To enhance SE, two evolutions were recently proposed: on the one hand the more revolutionary flexible grid architecture [1], on the other hand the more straightforward time domain hybrid modulation formats (TDHMF) approach [2].…”
Section: Introductionmentioning
confidence: 99%